The experience of fear and psychological distress among migrants in Spain - Milton Alexander López-de-León; Nina Hansen; Sabine Otten; Susana Puertas Valdeiglesias (Frontiers in Psychology)
ObjectivesPsychological distress is an unpleasant state with both emotional and psychological manifestations. Migrants are prone to facing psychological distress. Previous research investigated the risk factors migrants face when integrating in a new society. However, little attention was paid to the role of experienced fear. Therefore, this study aimed to investigate the prevalence of psychological distress of migrants and its link with the number of situations migrants may have experienced fear during and after the migration journey in addition to previously identified risk factors among migrants in Spain.Methods381 migrants from different nations participated in a correlational study. Besides demographic information, we assessed four self-reported risk factors (immigration status, employment, social network, and Spanish proficiency). The relevant number of situations in which migrants experienced fear was assessed with four items (sum score) and psychological distress with the K10 Kessler Psychological Distress Scale. Important to note, the K10 did not include items assessing fear.Results31.3% of migrants experienced severe levels of psychological distress. Three risk factors (immigration status, employment, and social network) and the sum score of fear-experienced situations correlated with psychological distress. A step-wise regression analysis (based on 10,000 Bootstrap samples) accounts for 15% of the variance in psychological distress, suggesting that (1) age (but not gender), (2) none of the risk factors, but (3) the sum score of fear-experienced situations showed a significant effect on psychological distress. Importantly, we assessed the amount of fear triggering situations migrants may have experienced (in contrast to general anxiety which is often measured and included in psychological distress scales).ConclusionsThe current study provides first evidence that various situations in which migrants experienced fear during and after their journey to Spain were associated with higher levels of psychological distress; more strongly than previously studied risk factors. We discuss the importance of differentiating between past fear to prevent trauma and current fear (e.g., of mafias and of feeling sick) in reception centers to help migrants navigate the new cultural context. Focusing on the mental health needs of migrants after arrival could be a promising first step to stimulate integration more sustainably.